Persepsi Wanita Berisiko Kanker Payudara tentang Pemeriksaan Payudara Sendiri di Kota Semarang, Jawa Tengah - Ophi Indria Desanti, IM. Sunarsih, Supriyati (Fakultas Kedokteran Universitas Gadjah Mada, 2010)
Background: Breast cancer is the main cause of death due to cancer at Semarang City. Breast cancer can be detected through breast self-examination. Perceptions about about benefit as well as perception about constraints of breast self-examination affect behavior of breast self-examination. This study is carried out to women with relatively high risk of having breast cancer.Objective: The study aimed to identify perception of women with risk of breast cancer about breast self-examination and identify relationship between that perception and behavior of breast self-examination.Methods: This was an analytical study with cross sectional design. Samples consisted of 384 women with risk of breast cancer at 10 villages of Semarang City taken with multistage random sampling method. Data were obtained through questionnaire of perception and behavior of breast self-examination of respondents that had got ethical clearance from Ethical Commission Council of Gadjah Mada University. Data analysis used chi-square and logistic regression.Results: Only 52.3% of respondents had breast self-examination. As much as 25.2% had positive perception about the benefit of doing breast-self examination; and 70.1% had negative perception about constraints of breast self-examination. Variables of perception about benefit (p=0.022) and about constraints (p=0.015) had relationship with behavior of breast self-examination. The result of logistic regression test showed that variables that were significant were confounding variables, i.e. level of knowledge (p=0.037), education (p=0.009) and information about breast self-examination (p=0.000).Conclusion: Variables related to behavior of breast self-examination were confounding variables, i.e. level of knowledge, education, and information about breast self-examination.Keywords: breast cancer, perception, breast self-examination